26. THE CURRENT SITUATION OF KNOWLEDGE AND PRACTICE OF NURSES AND MIDWIVES ON FALL PREVENTION FOR PATIENTS AT HUNG VUONG GENERAL HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Background: A fall is one of six medical incidents that can adversely affect patients' conditions, increase disability rates, and increase treatment costs.Objective: To describe the current status of knowledge and practices of nurses and midwives regarding fall prevention for patients at Hung Vuong General Hospital in 2024 and to identify some related factors.Methods: A cross-sectional study was conducted with 160 nurses and midwives at Hung Vuong General Hospital from March to December 2024. A self-administered questionnaire on knowledge and practice of fall prevention was designed, and SPSS software was used to analyze the data.Results: There are 160 participants in the study. The proportion of nurses and midwives with full knowledge of fall prevention is 49,4%, and Mean±SD = 16,7±6,5, while Mean±SD = 3,81±0,63 and 87,5% is the percentage of nurses and midwives who get good practice. Knowledge related to the type of training, department, and updating method. There are also connections between practice and department, the number of patients cared for a day, updating methods, and level of interest in fall prevention. There was no association between knowledge and practice in fall prevention.Conclusion: The knowledge of fall prevention among nurses and midwives remains low, while their practice is relatively good. Enhancing knowledge and practice among this workforce is essential through short-term or continuous training programs. In addition, training programs should be designed to incorporate clinical simulations, and a fall monitoring system should be established based on nursing quality indicators.
Keywords: Fall prevention; knowledge; practice; nursing; midwife.